The Mediating Effect of the Information Technology Adoption on the Relationship Transformational Leadership and Knowledge Management in the Royal Malaysian Navy - Shaiful Nizam, Abdul Manan (2025)
This study examines the relationship between transformational leadership, information technology (IT), and knowledge management (KM) adoption within the Royal Malaysian Navy (RMN). It addresses a gap in understanding ow leadership and IT mediate KM adoption in military settings, where challenges such as insufficient leadership and poor strategic alignment persist. The research explores how transformational leadership fosters KM processes, mediated by IT, to enhance decision-making and organizational efficiency. Using a cross-sectional survey, data were collected from 336 Senior Enlisted Leaders (SELs) at RMN’s Lumut Naval Base using structured questionnaires. Key constructs, including leadership styles, KM, and IT adoption, were measured with validated tools such as the Multifactor Leadership Questionnaire (MLQ) and Technology Acceptance Model (TAM). SPSS was used for data analysis. The findings demonstrate that transformational leadership significantly impacts the knowledge management (KM) process (β =0.567, p < 0.001). Information technology (IT) adoption also plays a key role, showing a positive and significant relationship with KM (β = 0.193, p < 0.001). Furthermore, IT partially mediates the relationship between transformational leadership and KM processes, as indicated by the reduction in the direct relationship when IT is included in the model. Correlation analyses reveal that KM is moderately correlated with transformational leadership (r = 0.479, p < 0.001) and IT (r = 0.354, p < 0.001), while the relationship between transformational leadership and IT is weaker (r = 0.179, p = 0.001). These results confirm that leadership style and IT adoption are critical enablers of effective KM practices. Transformational leadership fosters trust and collaboration, while IT enhances knowledge-sharing mechanisms, creating a synergistic effect in organizational knowledge processes. The study is limited to a single military organization and relies on self-reported data, potentially introducing biases. Future research could explore other military and public organizations, considering additional mediating factors like organizational culture or environmental influences. Practical recommendations include improving IT infrastructure, implementing training programs to support leadership initiatives, and fostering a KM-focused organizational culture. These efforts enhance both theoretical and practical understanding of leadership and KM in military settings, paving the way for stronger frameworks in knowledge-driven environments.